2018
DOI: 10.3390/su10093345
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Farmers’ Perceptions and Behaviors towards Farmland Quality Change in Northeast China: A Structural Equation Modeling Approach

Abstract: Farmland protection is the most important land science research issue in developing countries, especially in China, due to serious land degradation. This paper aimed to reveal the causal chain among driving factors, farmers' land protection perceptions, behavioral responses, and land quality change by applying a structural equation model (SEM), based on a cross-sectional dataset of 238 households surveyed, and matched plot soil sample results in the Sujiatun District, in Liaoning province, China. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Of the three factors related to farmers' demographic characteristics, we found that age did not have a significant impact on their knowledge and perceptions. Similarly, several other studies conducted in different parts of the world found that age did not affect farmers' perception levels [70][71][72]. However, recent studies conducted in Indus River Basin of Pakistan and Bangladesh reported that younger farmers were more interested in the adoption of AF than old farmers as they are more knowledgeable about the benefit of applying advanced technology in farming such as AF [23,73].…”
Section: Factors Affecting Perceptions Of the Respondentsmentioning
confidence: 84%
“…Of the three factors related to farmers' demographic characteristics, we found that age did not have a significant impact on their knowledge and perceptions. Similarly, several other studies conducted in different parts of the world found that age did not affect farmers' perception levels [70][71][72]. However, recent studies conducted in Indus River Basin of Pakistan and Bangladesh reported that younger farmers were more interested in the adoption of AF than old farmers as they are more knowledgeable about the benefit of applying advanced technology in farming such as AF [23,73].…”
Section: Factors Affecting Perceptions Of the Respondentsmentioning
confidence: 84%
“…Traditional statistical methods are not capable of solving the causal relationships often present when dealing with surveys that have multiple cases [79]. In this regard, the Structural Equation Model (SEM) was used to estimate latent variables that cannot be observed directly, and to measure the causal relationships between them.…”
Section: Methodology Of Analysismentioning
confidence: 99%
“…This characteristic of group participation for improving household livelihood is in contrast to a prior study (Taruvinga & Fraser, 2009). Knowledge, training, and environmental policy information also play key roles in farmer activities (H. Liu & Luo, 2018). The adoption of information technology (Suvedi et al, 2017) through education and training (Sullivan-Wiley & Gianotti, 2018) can be an incentive for increasing the knowledge of independent palm smallholders (Lastra-Bravo et al, 2015).…”
Section: The Farmers' Characteristicsmentioning
confidence: 99%